2017
DOI: 10.3390/ijms18040745
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAs in Myocardial Infarction: From Molecular Mechanism to Clinical Application

Abstract: MicroRNAs (miRNAs) are a class of small single-stranded and highly conserved non-coding RNAs, which are closely linked to cardiac disorders such as myocardial infarction (MI), cardiomyocyte hypertrophy, and heart failure. A growing number of studies have demonstrated that miRNAs determine the fate of the heart by regulating cardiac cell death and regeneration after MI. A deep understanding of the pathophysiology of miRNA dependent regulatory pathways in these processes is required. The role of miRNAs as diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 123 publications
(164 reference statements)
1
100
0
2
Order By: Relevance
“…Recently, dysregulation of miRNAs was reported in the development and progression of MI . miRNA‐29 was found to be decreased post‐MI, while miR‐21 was proved upregulated during cardiac stress .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dysregulation of miRNAs was reported in the development and progression of MI . miRNA‐29 was found to be decreased post‐MI, while miR‐21 was proved upregulated during cardiac stress .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several cardiac-specific miRNAs have been identified to play important roles in the development of cardiovascular diseases 69. Among these miRNAs, four cardiac-enriched miRNAs (miR-208, miR-499, miR-1 and miR-133) are consistently found to be increased in the plasma of patients with AMI 70.…”
Section: Summary Of Cardiac Biomarkersmentioning
confidence: 99%
“…The human genome is enriched with polymorphisms that result in different phenotypes. Accumulating evidence suggests that miRNAs play important regulatory roles in different diseases including cardiovascular disease . The polymorphisms in miRNAs have been linked to susceptibility to cardiovascular diseases such as myocardial infarction and coronary heart disease .…”
Section: Discussionmentioning
confidence: 99%
“…As miR‐499‐5p is highly expressed in cardiac tissue and participates in the maintenance of cardiac survival and function, it is reasonable to propose that polymorphism rs3746444 may contribute to the susceptibility of heart diseases. For the polymorphism rs3746444 (A→G) of hsa‐mir‐499, the few previous studies have shown that the variant genotype GG of this SNP was significantly associated with the increased risk of cancer and dilated cardiomyopathy, but most of the studies found no significant association with the increased risk of cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation